Pemberdayaan Masyarakat Melalui Gerakan Edukasi Transportasi Perkeretaapian - Prasetiyo, Alfian Yuda; Priyanto, Sapto (Institut Transportasi dan Logistik Trisakti, 2023)
The development of railway technology and the safety of railway transportation are shared responsibilities between the government and the community. However, the development of this technology is not widely known by the general public, especially those outside the area where railway transportation is organized. Therefore, there is a need for education and knowledge sharing related to technological developments in railway transportation such as the Electric Rail Train commuter line, Mass Rapid Transit/Integrated Motorway, Light Rail Transit, and High Speed Rail and railway transportation safety, especially at level crossings. The methods used in community service activities consist of preparation and education in class with interactive media, namely videos and pictures. Apart from that, education is carried out in the Madiun Indonesian Railway Polytechnic lab by looking directly at station simulators and train traffic control simulators, looking at the types of trains, and seeing railway infrastructure such as train tracks, signals, and level crossings. The results of the evaluation of the implementation of community service activities regarding railway transportation education show that the students of Al Izzah Nganjuk Islamic High School gained an understanding of railway transportation, especially in the areas of technological development of railway transportation and safety on level lines.